Pemasangan Tempat Sampah dan Plang Sampah di Wilayah Kelurahan Sepinggan - Bima Aditya Nugroho; Abhi Sultan Maulana Arifin; Angga Dwi Saputra; Billy Sagala; Davin Feliano Merentek; Della Devitriani; Desti Dwi Chayati; Dina Aryani; Ahmadrudhani Ahmadrudhani; Oscarius Pape Oly; Wahyu Ismail Kurnia; Wagimin Wagimin; Muhamad Hasyim Tuankotta (Abdimas Universal, 2024)
Raising public awareness to live a cleaner and waste-free life is our common hope. Lack of knowledge and awareness among the people of Sepinggan RT 18 regarding the importance of protecting the environment from waste. To raise public awareness about caring for the environment, it is necessary to provide education and provide an example to the public, one of which is making organic and inorganic waste bins in order to change people's mindset habits. Sepinggan Subdistrict RT 18 is a beautiful village but unfortunately there is still a lot of rubbish scattered and scattered everywhere. Therefore. The author made organic and inorganic rubbish bins to be useful in the RT 18 community, Sepinggan sub-district, to dispose of rubbish in its place.